Fractional Absorption of Iron from Crickets Consumed with Refined or Whole Meal Maize Porridge in Young Adult Women (OR07-06-19). (13th June 2019) - Melse-Boonstra, Alida; Mwangi, Martin; Oonincx, Dennis G A B; van Loon, Joop J A; Cercamondi, Colin; Utami, Dessy; Gunawan, Lidyawati; Veenenbos, Margot; Zeder, Christophe; Zimmermann, Michael; Dicke, Marcel
Abstract: Objectives: Edible insects are considered as an alternative source of proteins, but in addition are also rich sources of minerals. However, no studies have investigated the bioavailability of minerals from edible insects in humans. House cricket ( Acheta domesticus ) is an edible insect species that is commonly consumed in low and middle income countries where the prevalence of iron deficiency and anaemia is relatively high. We aimed to assess the fractional iron absorption of iron from house crickets in humans after addition to either a refined (low-phytate) or a whole meal (high-phytate) maize porridge meal. A second objective was to assess the fractional iron absorption from maize porridge meals when crickets were added. Methods: A single blind randomized cross-over trial was conducted. We recruited 24 females (18–30 years) with serum ferritin < 25 ng/mL and body weight < 65 kg. Six different meals with equivalent amounts of iron were randomly administered to each participant in two series, consisting of either refined (low-phytate) or whole meal (high-phytate) maize porridge with A) intrinsically 57Fe labelled house crickets; B) 58FeSO4; and C) unlabelled house crickets and 54FeSO4. Fractional iron absorption was determined by measuring shifts in Fe isotope ratios incorporated into erythrocytes that were collected before and 14 days after administration of each series of experimental meals. Results: For refined maize porridge, mean fractional absorption of iron from meal B was higher (13.55%; P < 0.001) than from meals A (1.99%) and C (3.12%). As expected, iron absorption was significantly lower from meals prepared from whole meal maize flour as compared to those prepared from refined flour ( P < 0.001). For whole meal maize porridge, fractional absorption of iron from meals A, B and C was 1.31%, 3.12% and 2.30%, respectively. Conclusions: Fractional absorption of iron from edible house crickets added to maize porridge was generally low, and addition of crickets to refined maize porridge reduced fractional iron absorption from the meal. Before promoting edible insects as an alternative source of iron, further investigation into their anti-nutritional properties is required. Funding Sources: Wellcome Trust, UK.